2008
DOI: 10.1016/j.molonc.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression and hypoxic up‐regulation of neuroglobin in human glioblastoma cells

Abstract: A B S T R A C TNeuroglobin is a recently identified globin molecule that is expressed predominantly in the vertebrate brain. Neuroglobin expression increases in oxygen-deprived neurons, suggesting it protects neurons from ischemic cell death. We report that neuroglobin transcript and protein are expressed in human glioblastoma cells, and that this expression increases in hypoxia in vitro. We also show that neuroglobin is up-regulated in hypoxic microregions of glioblastoma tumor xenografts. Our finding of hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 64 publications
3
34
0
2
Order By: Relevance
“…The difference in the associations between NGB and MB with VEGFa may imply that different regulatory mechanisms control expression of these two globins. The hypoxic stress of lung cell lines in this study resulted in induction of NGB and MB expression, confirming previous studies [18,22]. Moreover, NGB co-expressed with carbonic anhydrase IX (CAIX) in various tumor types [33], while MB link to hypoxia was demonstrated in breast cancer samples [34,35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The difference in the associations between NGB and MB with VEGFa may imply that different regulatory mechanisms control expression of these two globins. The hypoxic stress of lung cell lines in this study resulted in induction of NGB and MB expression, confirming previous studies [18,22]. Moreover, NGB co-expressed with carbonic anhydrase IX (CAIX) in various tumor types [33], while MB link to hypoxia was demonstrated in breast cancer samples [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…However, the information on the expression profiles of MB and NGB in human cancer is limited. NGB has been reported to co-localize with hypoxia marker, pimonidazole, in the glioblastoma xenograft tumors [18]. MB immunoreactivity is frequently used as a marker in sarcomas and rhabdomyosarcomas to confirm a myogenic phenotype of the tumor cells [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It is also believed to have a crucial function in oxygen transport and nitric oxide scavenging activities [2-4, 7, 10-12]. NGB expression is upregulated in some conditions such as cancer [13], aging [14], neuronal degeneration [15,16], and brain ischemia [6,17]. However, the underlying mechanism remains unclear [11,18].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that Ngb and Cygb are expressed in human GBM cell lines (18)(19)(20), as well as in human primary tumors including brain tumors (19). In this study, we examined whether hemoglobins (α, β, γ, δ, ζ and ε) are also expressed in human GBM cell lines.…”
Section: Introductionmentioning
confidence: 99%